MY CART (5)

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: R

There are no items in this cart.
Continue Shopping

X

“Hurray! You have won the gift voucher. Redeem your points now."

X

Composite Functions

Another useful combination of two functions f and g is the composition of these two functions. Let f : X → Y and g : Y → Z be two functions.

                       composite-functions

We define a function h : X → Z by setting h(x) = g(f(x). To obtain h(x), we first take the f-image f(x), of an element x in X so that f(x) ε Y, which is the domain of g(x) and then take the g-image of f(x), that is, g(f(x)), which is an element of Z. The scheme is shown in the figure.

The function h, defined above, is called the composition of f and g and is written gof. Thus (gof)(x) = g(f(x)). Domain of gof = {x : x in domain f, f(x) in domain g}.

e.g. Let f : R → R be a function defined by f(x) = x2 + 4 and g[0, ∞) → R be a function defined by g(x) = √x. Then gof(x) = g(f(x)) = √(x2 + 4). Domain of gof = R. Thus we have gof : R → R defined by (gof)(x) = √(x2 + 4). Similarly, we shall have fog : [0, ∞) → R defined by (fog)(x) = x + 4. Note that (gof)(x) ≠ (fog)(x).

Illustration: Two functions are defined as under:

             equation-for-fog-and-gof

Find fog and gof.

Solution: (fog)(x) = f(g(x))  equation-for-fog

 

                Let us consider, g(x) < 1 :

                (i) x2 < 1, -1 < x < 2  =>  -1 < x < 1, -1 < x < 2 => -1 < x < 1

                (ii) x2 + 2 < 1, 2 < x < 3  =>  x < -1, 2 < x < 3 => x = φ

                Let us consider, 1 <  g(x)  <  2,

                (iii) 1 < x2 < 2,  -1 < x < 2

                        => x ε [-√2, -1) υ (1,√2] ,  -1 < x < 2  =>  1 < x < √2

                (iv) 1 < x+2 < 2, 2 < x < 3 => -1 < x < 0, 2 < x < 3, x = φ

                   equation-for-gof

                Let us consider -1 < f(x) < 2 :

                (i)     -1 < x+1 < 2, x < 1 => -2 < x < 1, x < 1 => -2 < x < 1

                (ii)    -1 < 2x+1 < 2, 1 < x < 2 => -1 , x < ½, 1 < x < 2 => x= φ

                Let us consider 2 < f(x) < 3:

                (iii)    2 < x+1 < 3 ,  x < 1 => x < 2 , x < 1 => x = 1

                (iv)   2 < 2x+1 < 3, 1 < x < 2 => 1 < 2x < 2, 1 < x < 2

                        => ½  <  x  1 , 1 < x < 2 => x = φ

                             equation-g(f(x))

                If we like we can also write g(f(x)) = (x+1)2, -2 < x < 1.

To know more about the study material of engineering and medical exams, please fill up the form given below:

We promise that your information will be our little secret. To know more please see our Privacy Policy
We promise that your information will be our little secret. To know more please see our Privacy Policy

OR

Signing up with Facebook allows you to connect with friends and classmates already using askIItians. It’s an easier way as well. “Relax, we won’t flood your facebook news feed!”